An Analytical Method for Determining the Residual Strength of Reinforced Concrete Beam-Slab Specimens - Wang, Yong; Chen, Zhenxing; Huang, Zhaohui; Gu, Aolin; Han, Guanxu; Liu, Weixin; Zhang, Yajun; Zhong, Bo (Frontiers in Built Environment, 2022)
This paper proposed one new method to determine the residual ultimate loads of the fire-damaged beam-slab specimens. Based on the conventional yield line method, the stiffness and deflection of the edge beam was considered to establish the theoretical method, and the residual ultimate loads of several beam-slab specimens in the literature were analyzed, and the predicted results were compared to the experimental results. Results show that the conventional simply-supported and fixed-end yield line method tended to underestimate or overestimate the residual ultimate loads of the specimens, and the present method can reasonably predict the ultimate loads of the beam-slab specimens.